2002
DOI: 10.1099/0022-1317-51-1-42
|View full text |Cite
|
Sign up to set email alerts
|

Conditions that may affect the results of susceptibility testing of Mycobacterium tuberculosis to pyrazinamide

Abstract: Pyrazinamide (PZA) is an important front-line anti-tuberculosis drug that is active only at acid pH. However, acid pH causes signi®cant dif®culty for PZA susceptibility testing. A common problem in PZA testing is false resistance caused by large bacterial inocula. This study investigated the relationship of false resistance to numbers of bacilli, pH and other factors that potentially affect susceptibility to PZA. Large inocula (10 7±8 bacilli=ml) of M. tuberculosis H37Ra caused signi®cant increase in medium pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
198
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(212 citation statements)
references
References 12 publications
8
198
0
6
Order By: Relevance
“…This was expected, as PZA has less activity on young, growing cultures at acid pH (5 . 5) than on old cultures (Zhang et al, 2002). These results suggest that the level of oxygen has an effect on PZA activity such that the lower the oxygen level, the greater the PZA activity.…”
Section: Resultsmentioning
confidence: 47%
See 2 more Smart Citations
“…This was expected, as PZA has less activity on young, growing cultures at acid pH (5 . 5) than on old cultures (Zhang et al, 2002). These results suggest that the level of oxygen has an effect on PZA activity such that the lower the oxygen level, the greater the PZA activity.…”
Section: Resultsmentioning
confidence: 47%
“…20 %) where tubercle bacilli grow well. PZA is a peculiar and unconventional drug that does not kill growing cultures very well, but kills old, non-growing cultures with less energy reserves more effectively (Zhang et al, 2002). In this study we have shown that anaerobic or hypoxic conditions, which do not allow tubercle bacilli to grow, enhanced the activity of PZA (Fig.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Additionally, due to the need for acidic conditions in pyrazinamide drug susceptibility testing, this is not routinely performed in the laboratory (Zhang et al, 2002). Hence, the treatment of M. bovisinfected patients with the front-line drug regimen is not only presumed to be totally inadequate but is also believed to lead to the emergence of drug-resistant mycobacterial strains.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its remarkable sterilizing activity in vivo, [13,14] it is not active against MTB under 'normal' culture conditions near neutral pH, [15]. It is only active at acid pH [16] an environment that is produced during active inflammation, and its activity is closely related to the acidity of the medium [7,17]. Even at acid pH 5.6, PZA kills MTB slowly and incompletely with no more than 76% of the bacterial population being killed by 1000 mg/L PZA, [18] which is 10-12 times higher than the already high minimum inhibitory concentration (MIC) of 50-100 mg/L [12].…”
Section: Introductionmentioning
confidence: 99%